DISCLOSURE PRACTICES AND EFFORTS TOWARD PROPOSING I-ZKDI: A CASE OF MALAYSIAN RELIGIOUS NON-PROFIT ORGANISATION - Sapingi, Raedah (International Journal of Psychosocial Rehabilitation, 2020)
As a religious non-profit organization, Zakat institutions (ZIs) in Malaysia facing dilemma due to issues raised by the public through media, commenting the ZIs credibility in handling the contributors’ money and reporting the zakat information, especially on disbursement part i.e. how the zakat money is being spent. Issues inconsistencies of disclosure practices, accessibility and availability of annual reports of Malaysian ZIs have offered many areas of reporting to be examined. These scenarios have sparked public debates regarding the accountability and transparency of ZIs in disclosing zakat information, especially for public viewing. Hence, this paper intends to gain an insight of zakat managers (ZMs), zakat payers (ZPs) and zakat recipients (ZRs) with regard to current disclosure practices of ZIs, and to identify and propose disclosure items that the users and panel experts consider important to be disclosed by ZIs in their annual reports. In answering these objectives, a semi-structured interview with ZMs, ZPs and ZRs were conducted and a Delphi technique was employed to gather the list of disclosure items. The findings reveal there were differences in opinions between the users and 25 items were proposed by the participants during survey interview. Finally, 96 disclosure items with five categories were agreed and confirmed by the expert panel via Delphi technique and be proposed as i-ZkDI. An item labelled as “total zakat disbursement for the year” was gained the highest score and in contrast, an item “Information on training attended by BODs/BOTs/CMs” received the lowest mean score rated by the Delphi members.